“‘Downton Abbey’ in Italian: Not Quite the Same” - Sandrelli, Annalisa (Status Quaestionis, 2017)
Language use in the well-known British period drama Downton Abbey is very interesting from many points of view. As the story is set in the Edwardian era, the dialogues are characterised by archaic vocabulary and idioms; moreover, they reflect regional and social differences, as the series portrays the aristocratic Crawley family and their servants living in the (fictional) country estate of Downton Abbey. In the light of the importance of diachronic, diatopic and diastratic variation in the series, this paper investigates to what extent these features have been reproduced in the Italian dubbed dialogues, by drawing on a corpus of 16 episodes from the first three seasons.